Cointegration of Macroeconomics Variables and Dow Jones Industrial Average Index on the Composite Stock Price Index In 2015-2019 - Frisca Novia Sukmawati; Nadia Asandimitra Haryono (Journal of Business and Management Review, 2021)
This research examines the cointegration of macroeconomic variables and the Dow Jones Industrial Average Index toward IHSG. The Sampling data used is non probability sampling techniques by using historical monthly data from January 2015 to December 2019. The method used in this study are Augmented Dickey-Fuller Test for stationarity test, Johansen Test for Cointegration, and Error Correction Model for short-term relationships with eviews 10. The findings showed that DJIA Index not cointegrated with IHSG because investors are more responsive to global market and domestic sentiment. Exchange rates not cointegrated with the IHSG because exchange rate and IHSG movements do not always had a negative relationship. Interest rates are not cointegrated with IHSG because most of the sectors in the IDX affected by external sentiment than interest rates. Meanwhile, inflation have a cointegration relationship but does not have a short-term relationship with IHSG because inflation is generally known as a continuous increase in the price of goods as a whole. Crude oil have a cointegration relationship but does not have a short-term relationship with IHDG, which implies that an increase or decrease in crude oil in the short term can not affect IHSG.